The Paradox of Love. - Bruckner, Pascal (Princeton University Press, 2012)
The sexual revolution is justly celebrated for the freedoms it brought--birth control, the decriminalization of abortion, the liberalization of divorce, greater equality between the sexes, women's massive entry into the workforce, and more tolerance of homosexuality. But as Pascal Bruckner, one of France's leading writers, argues in this lively and provocative reflection on the contradictions of modern love, our new freedoms have also brought new burdens and rules--without, however, wiping out the old rules, emotions, desires, and arrangements: the couple, marriage, jealousy, the demand for fi.